PENGARUH KOMPETENSI, PENGALAMAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DINAS TOWER DAN GROUND CONTROL MAKASSAR AIR TRAFFIC SERVICE CENTER (MATSC). - Vivid Violin (STIE AMKOP, 2020)
Influence of competence, experience and work culture concerning work performance of employe tower and ground control unit at Makassar Air Traffic Service Center (MATSC). The purpose of this research was to examine the influence of competence, experience and work culture concerning work performance of employe tower and ground control unit at Makassar Air Traffic Service Center (MATSC). Sampling methode used total sampling with 50 employe of air traffic controller who has valid of licence and rating related tower and ground control unit at Makassar Air Traffic Service Center (MATSC). The result of this research is indicate that there is a positif and significant relation of variable work culture and experience concerning employe working performance tower and ground control unit at Makassar Air Traffic Service Center (MATSC). While competence variable does not have signifacant relation concerning employe working performance tower and ground control unit at Makassar Air Traffic Service Center (MATSC). Keyword : competence, experience, work culture, work performance